Estudio del uso de la plataforma virtual Zoom como herramienta educativa en la enseñanza – aprendizaje entre estudiantes y docentes de la carrera de Comunicación Social de la Universidad Nacional de Loja durante el periodo octubre 2020 – marzo 2021. - Riofrío Apolo, Anahí del Cisne (2022)
This research studies the use of the Zoom platform as an educational tool in the teaching-learning process between students and teachers of the Communication career of the National University of Loja during the period October 2020 - March 2021. Nowadays, the advance of the Internet and the use of Information and Communication Technologies (ICT's) transforms the way people learn, teach, communicate and live in the classroom, (ICT's) transform the way in which people learn, teach, communicate and coexist in the classroom, therefore, the general objective of this research was to study the use of the Zoom virtual platform and how it influences the teaching-learning process among students and teachers of the Communication career of the UNL. Three objectives were proposed: to establish the advantages and disadvantages of the Zoom platform in the interaction between students and teachers; to determine whether the Zoom platform is an adequate tool for learning the curriculum, in accordance with the needs established in the analytical plans of the main technical subjects taught; and to analyze the impact and adaptability that teachers and students have had in the change from face-to-face to virtual learning and how this influences the academic quality of the career. In order to meet these objectives, a mixed methodology was applied, that is, qualitative-quantitative. Two research techniques were determined: The first one is the interview directed to pedagogy and technology specialists which served to find out the benefits, impact and adaptability of the Zoom platform, and the second is the survey which identified the teaching - learning process among teachers and students. Finally, as an alternative proposal, the creation of a user manual for the correct use of the Zoom platform in the learning of the disciplines taught in the communication career of the UNL was suggested. Keywords: TIC's, Digital Platforms, Zoom Platform, Teaching - Learning.